ANALYZING THE IMPACT OF DIGITAL ECONOMIC EXPANSION ON RESOURCE UTILIZATION AND ENVIRONMENTAL SUSTAINABILITY IN UZBEKISTAN (Journal of Universal Science Research, 2024)
This study investigates the intricate relationship between digital economic expansion, resource utilization, and environmental sustainability in Uzbekistan. As the country advances its digital economy, understanding the environmental consequences of this growth becomes crucial for policy-making. The research explores how Uzbekistan’s digital-driven GDP growth impacts resource consumption, particularly focusing on energy usage, water resources, and land utilization, alongside environmental degradation indicators such as CO2 emissions and pollution levels.